Application of tiens golden harvest fertilizer in Hibiscus sabdariffa L. - . Zuyasna; Marai Rahmawati; . Nurmasyitah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The research was conducted to determine the effect of Tiens Golden Harvest (TGH) fertilizer concentration and the varieties on growth and yield of Roselle, and also to examine the interaction between the two factors. The research was conducted in the Experimental field of Agriculture Faculty, Syiah Kuala University, Darussalam Banda Aceh, from June 2010 to November 2010. The material used was Roselle seed varieties, manure, TGH, using Factorial Randomized Block Design 4 x 2 in three replications. The first factor used was TGH fertilizer concentration (i.e. 0;5;10;15 ml/l) and the second factor was Roselle varieties (Sabdariffa and Altissima). So, we were conducted 8 combinations of treatments which were designed into 24 units of experiments. The concentration of TGH fertilizer significantly effect on plant height on 15 and 30 days after planting (DAP), the diameter of the base plant’s stem on 15 DAP, the number of calyx per plant and the weight of calyx without seeds per plant for 5 times harvest. The best growth and yield of Roselle plant result was found in using TGH 10 ml/l of water. After 5 times harvest, using 10 ml/l TGH we got 54.93 calyx/plant with 43.33 dry weights. Variety significantly effect on the plant length on 15 and 50 DAP, the diameter of the stem on 15 and 50 DAP, and Roselle calyx fresh weight for 5 times harvest. The growth and yield of Altissima variety on this experiment was better than Sabdariffa variety. For 5 times harvest of Altissima variety, the number of calyces per plant was 46.47, the fresh weight was 457.60 g and dry weight was 39.09 g. There was a significant interaction between TGH fertilizer concentration and Roselle varieties on the stem diameter 50 DAP and the fresh weight of calyx. The best growth and yield of Roselle showed on the application of 10 ml/l TGH fertilizer to Altissima variety, with total fresh weight calyx was 457 g.